Palaeoenvironmental evolution in the coastal plain of Baixo Ribeira during the shell mounds occupation. - Bissa, Walter Mareschi; Ybert, Jean-Pierre; Catharino, Eduardo Luis Martins; Kutner, Miryam (Revista do Museu de Arqueologia e Etnologia, 2000)
Pollen and diatoms analyses in a peat bog from the Baixo Ribeira do Iguape region (São Paulo State, Brazil) showed expressive changes in the environmental conditions. Brackish waters connected to the sea covered this site before 3.250 years BP; after that a swamp forest developed. Sea presence is due to the marine transgression that culminated at 5.100 years BP. Lowering of sea level has been gradual from 5.100 years BP to the present, without major oscillations. This drastic change in environmental conditions can explain the distribution of the archaeological sites in this region, specially the presence of shell mounds 50 km away from the coast.